1988
DOI: 10.1111/j.1365-2621.1988.tb07824.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gluconic Acid on Enzyme Inactivation and Color Retention in Canned Apricots and Peaches

Abstract: Apricots, clingstone and freestone peaches packed in tin-free steel cans with up to 1.1% gluconic acid in the syrup retained better color than fruits packed without the acidulant. Up to 0.44% by weight gluconic acid did not affect heat resistance of peroxidase/polyphenoloxidase enzyme systems in apricots. Requirements for heat inactivation of enzymes increased with fruit maturity, from Frmc = 1.3 min with z = 16°C in canning ripe, to Franc = 7 min with z = 61.5"C in soft ripe apricots. Enzyme regeneration occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
1
11
1
Order By: Relevance
“…Interestingly, z-values may be influenced by the degree of ripeness and preparation method. Thus, Heil et al (1988) reported a wide variance in z-value of 16 and 61.5 1C for PPO of ripe and soft apricot prepared for canning. Differences in the kinetics of heat activation of PPO for different products may result from differences in their composition, reflective of their variety or the agronomic and climatic conditions under which they were grown.…”
Section: Article In Pressmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, z-values may be influenced by the degree of ripeness and preparation method. Thus, Heil et al (1988) reported a wide variance in z-value of 16 and 61.5 1C for PPO of ripe and soft apricot prepared for canning. Differences in the kinetics of heat activation of PPO for different products may result from differences in their composition, reflective of their variety or the agronomic and climatic conditions under which they were grown.…”
Section: Article In Pressmentioning
confidence: 94%
“…Of the studies on heat inactivation of PPO only a few have included the calculations of Arrhenius and the kinetic parameters of heat inactivation of PPO from various foods. These include apple (Stru¨bi, Escher, & Neukom, 1975), Sultana grapes (Aquilera, Oppermann, & Sanchez, 1987), apricot (Heil, McCarthy, & Merson, 1988), rice (Ansah, 1989) and mango (Askar, ElAshwah, Omran, & Labib, 1994). No information is available for pineapple puree on the quantitative effects of temperature and time on the inactivation of PPO which was the subject of this study.…”
Section: Introductionmentioning
confidence: 98%
“…It is difficult to compare them been reported earlier in the case of PPO from other sources such as cocoa bean (25), apples (6) and apricots (26). The heating of the enzyme at 65ЊC, however, almost totally inactivated the enzyme within 30 min (80% of the activity was lost in 30 min).…”
Section: Fig 3 Determination Of Dynamic Binding Capacity For Polyphmentioning
confidence: 91%
“…The increase in activity obtained by exposing PPO to harsher conditions has been called "latency of PPO" (4,6) or "enzyme regeneration" (2). Exposure to moderately high temperature has also been reported to cause such an increase (6,26). A clear understanding of this phenomenon at the molecular level is still missing.…”
Section: Fig 3 Determination Of Dynamic Binding Capacity For Polyphmentioning
confidence: 92%
“…However, the pH level required to produce an effect on the heat resistance of spores, acidifiying with citric acid, may confer to the product an excessive acid taste if citric acid is used as the acidulant (Rodrigo & Martínez, 1988). It has been shown how others acidulants, such as gluconic acid and its lactones, enhance the brightness and colour of certain fruits (Heil et al, 1988) or make it possible to use a lower pH with a smaller increase in acid taste (Malyniak & Meagher, 1990).…”
Section: Introductionmentioning
confidence: 99%